Enhanced physicochemical properties of chitosan/whey protein isolate composite film by sodium laurate-modified TiO2 nanoparticles. (15th March 2016) - Zhang, Wei; Chen, Jiwang; Chen, Yue; Xia, Wenshui; Xiong, Youling L.; Wang, Hongxun
Highlights: Sodium laurate-modified TiO2 was incorporated into chitosan/whey protein film. Modified nano-TiO2 improved the compatibility of whey protein and chitosan. Modified nano-TiO2 enhanced mechanical properties of chitosan/whey protein film. Modified nano-TiO2 reduced water vapor permeability of chitosan/whey protein film. Abstract: Chitosan/whey protein isolate film incorporated with sodium laurate-modified TiO2 nanoparticles was developed. The nanocomposite film was characterized by scanning electron microscopy, X-ray diffraction and differential scanning calorimetry, and investigated in physicochemical properties as color, tensile strength, elongation at break, water vapor permeability and water adsorption isotherm. Our results showed that the nanoparticles improved the compatibility of whey protein isolate and chitosan. Addition of nanoparticles increased the whiteness of chitosan/whey protein isolate film, but decreased its transparency. Compared with binary film, the tensile strength and elongation at break of nanocomposite film were increased by 11.51% and 12.01%, respectively, and water vapor permeability was decreased by 7.60%. The equilibrium moisture of nanocomposite film was lower than binary film, and its water sorption isotherm of the nanocomposite film fitted well to Guggenheim–Anderson–deBoer model. The findings contributed to the development of novel food packaging materials.